pH-Responsive polymer boosts cytosolic siRNA release for retinal neovascularization therapy - Shuai Guo; Chunhui Li; Changrong Wang; Xiaowen Cao; Xinyue Liu; Xing-Jie Liang; Yuanyu Huang; Yuhua Weng (Elsevier, 2024)
Small interfering RNA (siRNA) has a promising future in the treatment of ocular diseases due to its high efficiency, specificity, and low toxicity in inhibiting the expression of target genes and proteins. However, due to the unique anatomical structure of the eye and various barriers, delivering nucleic acids to the retina remains a significant challenge. In this study, we rationally design PACD, an A-B-C type non-viral vector copolymer composed of a hydrophilic PEG block (A), a siRNA binding block (B) and a pH-responsive block (C). PACDs can self-assemble into nanosized polymeric micelles that compact siRNAs into polyplexes through simple mixing. By evaluating its pH-responsive activity, gene silencing efficiency in retinal cells, intraocular distribution, and anti-angiogenesis therapy in a mouse model of hypoxia-induced angiogenesis, we demonstrate the efficiency and safety of PACD in delivering siRNA in the retina. We are surprised to discover that, the PACD/siRNA polyplexes exhibit remarkable intracellular endosomal escape efficiency, excellent gene silencing, and inhibit retinal angiogenesis. Our study provides design guidance for developing efficient nonviral ocular nucleic acid delivery systems.